Obesity in spontaneous spondylodiscitis: a relevant risk factor for severe disease courses - Benjamin Schoof (Nature Portfolio, 2020)
Abstract Spondylodiscitis is a serious and potentially life-threatening disease. Obesity is a risk factor for many infections, and its prevalence is increasing worldwide. Thus, the aim of this study was to describe characteristics of obese patients with spondylodiscitis and identify risk factors for a severe disease course in obese patients. Between December 2012 and June 2018, clinical records were screened for patients admitted for spondylodiscitis. The final analysis included 191 adult patients (mean age 64.6 ± 14.8 years). Patient data concerning demographics, comorbidities, surgical treatment, laboratory testing, and microbiological workup were analysed using an electronic database. Patients were grouped according to body mass index (BMI) as BMI ≥ 30 kg/m2 or < 30 kg/m2. Seventy-seven patients were classified as normal weight (BMI 18.5–24.9 kg/m2), 65 as preobese (BMI 25–29.9 kg/m2), and 49 as obese (BMI ≥ 30 kg/m2). Obese patients were younger, had a higher revision surgery rate, and showed higher rates of abscesses, neurological failure, and postoperative complications. A different bacterial spectrum dominated by staphylococci species was revealed (p = 0.019). Obese patients with diabetes mellitus had a significantly higher risk for spondylodiscitis (p = 0.002). The mortality rate was similar in both cohorts, as was the spondylodiscitis localisation. Obesity, especially when combined with diabetes mellitus, is associated with a higher proportion of Staphylococcus aureus infections and is a risk factor for a severe course of spondylodiscitis, including higher revision rates and sepsis, especially in younger patients.